INCIDENCE AND PREDICTORS OF SURGICAL SITE INFECTION FOLLOWING OPEN REDUCTION AND INTERNAL FIXATION OF LONG BONE FRACTURES - Dr. Eswara Reddy G; Dr. Shivakumar M S; Dr. Manjunath A N (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Surgical Site Infections (SSIs) are a major complication following orthopaedic procedures, particularly Open Reduction and Internal Fixation (ORIF) of long bone fractures. This was a study done to measure the incidence of SSIs and also to identify the independent predictors of SSIs in patients who underwent ORIF surgery due to long bone pathologies in a tertiary care hospital. Twelve months with the participation of 200 patients who received ORIF to treat a fracture of the femur, tibia, humerus, or forearm were practiced as a prospective observational study. Demographic, clinical, and intraoperative data were collected. The classification according to the Centers for Disease Control and Prevention (CDC) guidelines was used in categorizing SSIs. Predictors were determined using univariate and multivariate analysis of logistic regression. The general SSI incidence was 14 %, of which 9 % were superficial and 5 % deep infections. The results of univariate analysis revealed that diabetes mellitus, open fractures, anemia, and prolonged surgery are classical risk factors. Both diabetes and open fractures were independent predictors as confirmed by multivariate analysis (adjusted OR 2.98 and 2.72, respectively). The stratified models showed an infection rate as high as 32 % in higher-risk subgroups. Patient outcomes in orthopedic trauma surgery may be improved by interventions such as glycaemic control and enhancement of wound management policies.